An overview of hospital acquired infections and the role of the microbiology laboratory - Nazir, Asifa; Kadri, S. M. (International Journal of Research in Medical Sciences, 2017)
Every year, many lives are lost because of the spread of infections in hospitals. These nosocomial infections, also called hospital acquired infections (HAI) are infections that patients acquire during the course of receiving healthcare treatment for other conditions. HAIs are a cause of significant morbidity and mortality in patients receiving healthcare, and the costs direct and indirect of these infections deplete the already limited financial resources allocated to healthcare delivery.